Genomic imbalances in syndromic congenital heart disease - Miriam Coelho Molck; Milena Simioni; Társis Paiva Vieira; Ilária Cristina Sgardioli; Fabíola Paoli Monteiro; Josiane Souza; Agnes Cristina Fett‐Conte; Têmis Maria Félix; Isabella Lopes Monlléo; Vera Lúcia Gil‐da‐Silva‐Lopes (Brazilian Society of Pediatrics, 2017)
Objective: To identify pathogenic genomic imbalances in patients presenting congenital heart disease (CHD) with extra cardiac anomalies and exclusion of 22q11.2 deletion syndrome (22q11.2 DS). Methods: 78 patients negative for the 22q11.2 deletion, previously screened by fluorescence in situ hybridization (FISH) and/or multiplex ligation probe amplification (MLPA) were tested by chromosomal microarray analysis (CMA). Results: Clinically significant copy number variations (CNVs ≥300 kb) were identified in 10% (8/78) of cases. In addition, potentially relevant CNVs were detected in two cases (993 kb duplication in 15q21.1 and 706 kb duplication in 2p22.3). Genes inside the CNV regions found in this study, such as IRX4, BMPR1A, SORBS2, ID2, ROCK2, E2F6, GATA4, SOX7, SEMAD6D, FBN1, and LTPB1 are known to participate in cardiac development and could be candidate genes for CHD. Conclusion: These data showed that patients presenting CHD with extra cardiac anomalies and exclusion of 22q11.2 DS should be investigated by CMA. The present study emphasizes the possible role of CNVs in CHD.